rationalize the denominator 1 by root 7 minus root 6
Answers
Answered by
263
heya it's Aastha !!!!!
hope it help you@
hope it help you@
Attachments:
![](https://hi-static.z-dn.net/files/d7e/5427432b1078ce99d2c3ab5b2904ec71.jpg)
Answered by
321
Hi ,
1/( √7 - √6 )
= ( √7 + √6 )/[ (√7 - √6 )(√7 + √6 ) ]
= ( √7 + √6 )/ [ ( √7 )² - ( √6 )² ]
= ( √7 + √6 )/ ( 7 - 6 )
= √7 + √6
I hope this helps you.
: )
1/( √7 - √6 )
= ( √7 + √6 )/[ (√7 - √6 )(√7 + √6 ) ]
= ( √7 + √6 )/ [ ( √7 )² - ( √6 )² ]
= ( √7 + √6 )/ ( 7 - 6 )
= √7 + √6
I hope this helps you.
: )
Similar questions
India Languages,
8 months ago
Math,
8 months ago
Science,
1 year ago
English,
1 year ago
History,
1 year ago